-TEORI YANG MEMPENGARUHI PERTUMBUHAN DAN PERKEMBANGAN : TEORI YANG MEMPENGARUHI PERTUMBUHAN DAN PERKEMBANGAN - yurike bala; Radityah Rahman Pakudu; Sri Yulan Umar (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
Human growth and development is a complex process and is influenced by various factors. This article provides an overview of some of the theories that influence our understanding of human development. The theories discussed include psychoanalytic theory by Sigmund Freud, learning theory by Ivan Pavlov, John Watson, and B.F. Skinner, cognitive theory by Jean Piaget, social-cognitive theory by Albert Bandura, and systems ecology theory by Urie Bronfenbrenner. Psychoanalytic theory highlights the importance of childhood experiences and relationships with parents in shaping personal development. Learning theory emphasizes the role of learning and experience in individual growth, where environment and reinforcement play an important role. Cognitive theory explains the development of human thinking through different cognitive stages, with assimilation, accommodation and balance as the main concepts. Socio-cognitive theory highlights the role of social influence and observation in human development, in which individuals learn through a process of observing and imitating those around them. Finally, systems ecology theory emphasizes the importance of social and environmental context in shaping human development, with the interactions between various interrelated systems. Through an understanding of these theories, we can gain a more comprehensive insight into the factors that influence human growth and development. This study uses a qualitative research method which aims to explain a phenomenon in depth and is carried out by collecting data as deeply as possible besides that the purpose of this research is also as teaching material given to S1 Educational Technology students in semester 2 (even).